Tren Penelitian tentang Galleries, Libraries, Archives dan Museums (GLAM): Analisis Bibliometrik - Putra, Rona; Aswari, Redi (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This research is an analysis of research development trends on GLAM (Galleries, Libraries, Archives and Museums) which aims to determine: (1) the development of the number of Scopus publication databases on GLAM from 2010 - 2024; (2) core journals in the field of GLAM publications; (3) networking between authors in GLAM studies; (4) number of author citations related to GLAM; (5 Network Visualization Maps and Publication Overlays about GLAM (6) Publication Density Visualization Maps about GLAM. This research uses a literary observation method with bibliometric analysis. Data was collected using the Publish or Perish application from the Scopus database between 2010 and 2024 which was then visualized using VosViewer application. The research results found that there were 84 articles discussing GLAM. There were 4 core journals related to GLAM, namely Advances in Librarianship (Q3), Lecture Notes in Computer Science (Q2), Global Knowledge, Memory and Communication (Q2) and Journal of Information Science (Q2). From the visualization results, there are 5 main research clusters and themes in GLAM studies that have not been widely researched, namely "cultural Heritage Collections", "Digital Humanities", "GLAM Sector", "Interoperability", and "GLAM Labs".